A hybrid solution proposal for precast tunnel segments. (24th March 2021) - Trabucchi, Ivan; Smarslik, Mario; Tiberti, Giuseppe; Petraroia, Diego N.; Plizzari, Giovanni A.; Mark, Peter
Abstract: The construction of underground structures is playing a relevant role in modern society. As a result of noticeable tunnel boring machine (TBM) evolution, mechanized excavation methods are gaining increased market shares. TBM driven tunnels are generally used in combination with precast concrete segments as the main support system for reducing or minimizing surface disturbances during construction and to fulfill the project requirements with regards to quality, construction times, budget and safety. Within this framework optimization approaches strongly focused on these process parameters, rather than the general structural performance of the segments. However, improving the performance by using conventional reinforcement, High Performance Fiber Reinforced Concretes (HPFRCs) or a combination of such enables a possible reduction of the lining thickness or the amount of reinforcement. To this aim, this paper presents a new hybrid solution for precast tunnel segments with a reduced thickness, which leads to new perspectives in reducing the total amount of concrete, in decreasing the volume of disposal materials from the boring process as well as to minimize the TBM size. A parametric numerical study is developed for evaluating the effectiveness of proposed hybrid solution. The latter is based on high strength reinforced concrete in combination with HPFRC at the longitudinal joints, whose geometric configuration is properly modified to maximize the segment's bearing capacity.